(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Environmental racism causes marginalized groups to be exposed to environmental hazards which negatively affects their health. The relationship between environmental racism factors and impacts on health, focusing on breathing and mental health, is the main concern of this study. Objective: To look at the numbers to find out how environmental pollutants, socioeconomic level, where people live, access to healthcare, ongoing stress, and community strength change respiratory and mental health results. Methods: The research was done by interviewing 273 adults from urban and adjacent areas exposed to environmental dangers to different degrees. Persons involved filled out a structured questionnaire on the paper scales developed by Likert. Scores for each construct were summed together. Quality control checks were done and after that, the data were studied using normality tests, reliability analysis, Pearson correlations, and multiple regression models. Results: Normality tests revealed that many variables deviated a lot from what is usual. Analysis of reliability indicated that the scales were not very internally consistent. The relationships among variables were not very strong. The study discovered that greater exposure to environmental pollutants was related to lower mental well-being (β = -0.182, p = 0.017), but no significant predictors could be found for respiratory effects. Altogether, predictors were able to explain only a little of the differences in health outcomes. Conclusion: Being exposed to environmental pollutants negatively affects mental health in certain groups, yet a variety of factors cause these health disparities. Because sociological studies are not very reliable and explain little of human behavior, more careful measurement, and thorough research are required. Dealing with environmental racism by combining health policies and interventions is very important for achieving health equity.